Novel insights into phage biology of the pathogen Clostridioides difficile based on the active virome - Schüler, Miriam A.; Daniel, Rolf; Poehlein, Anja (Frontiers in Microbiology, 2024)
The global pathogen Clostridioides difficile is a well-studied organism, and researchers work on unraveling its fundamental virulence mechanisms and biology. Prophages have been demonstrated to influence C. difficile toxin expression and contribute to the distribution of advantageous genes. All these underline the importance of prophages in C. difficile virulence. Although several C. difficile prophages were sequenced and characterized, investigations on the entire active virome of a strain are still missing. Phages were mainly isolated after mitomycin C-induction, which does not resemble a natural stressor for C. difficile. We examined active prophages from different C. difficile strains after cultivation in the absence of mitomycin C by sequencing and characterization of particle-protected DNA. Phage particles were collected after standard cultivation, or after cultivation in the presence of the secondary bile salt deoxycholate (DCA). DCA is a natural stressor for C. difficile and a potential prophage-inducing agent. We also investigated differences in prophage activity between clinical and non-clinical C. difficile strains. Our experiments demonstrated that spontaneous prophage release is common in C. difficile and that DCA presence induces prophages. Fourteen different, active phages were identified by this experimental procedure. We could not identify a definitive connection between clinical background and phage activity. However, one phage exhibited distinctively higher activity upon DCA induction in the clinical strain than in the corresponding non-clinical strain, although the phage is identical in both strains. We recorded that enveloped DNA mapped to genome regions with characteristics of mobile genetic elements other than prophages. This pointed to mechanisms of DNA mobility that are not well-studied in C. difficile so far. We also detected phage-mediated lateral transduction of bacterial DNA, which is the first described case in C. difficile. This study significantly contributes to our knowledge of prophage activity in C. difficile and reveals novel aspects of C. difficile (phage) biology.